Release method evaluation for swift fox reintroduction at Bad River Ranches in South Dakota. Issue 4 (28th April 2015) - Sasmal, Indrani; Honness, Kevin; Bly, Kristy; McCaffery, Magnus; Kunkel, Kyran; Jenks, Jonathan A.; Phillips, Mike
<x xml:space="preserve">Abstract</x> Reintroductions have increasingly become effective at restoring populations of imperiled native wildlife. How animals are reintroduced into unfamiliar environments may have pronounced impacts on behavior, survival, and reproduction. We evaluated the influence of four release methods on survival rates of translocated swift foxes at Bad River Ranches (BRR) in western South Dakota: (1) hard‐release, (2) short‐soft‐release, (3) long‐soft‐release, and (4) captive born. A total of 179 foxes captured in Wyoming during 2002–2007 and in Colorado during 2006–2007 were released into BRR and the surrounding area. In addition, 43 pups born to foxes in the long‐soft‐release category were also released. All release methods incorporated a 14‐ to 21‐day quarantine period. Hard‐release foxes were released directly from a transport kennel, whereas short‐soft‐release foxes were released from soft‐release pens by opening the door and allowing the foxes to leave voluntarily. Long‐soft‐release foxes were held for more than 250 days on‐site in soft‐release pens through the winter and released in the following year in early summer. During 2002–2007, survival of reintroduced foxes differed significantly (p < 0.05) by age (adult vs. juvenile), release year, and release method. The short‐soft‐release method had the highest 60‐day post‐release survival probability compared with the other release methods. We did not detect any differences in mortality hazards between wild‐born and short‐soft‐release foxes. Reintroduction programs based on short‐soft‐releases are useful for restoring or augmenting populations to advance the conservation of the swift fox.